Professional Misfits: “You’re Having to Perform . . . All Week Long” - Brenda L. Beagan; Kaitlin R. Sibbald; Tara M. Pride; Stephanie R. Bizzeth (Open Journal of Occupational Therapy, 2022)
Background: Occupational therapy professes commitment to equity and justice, and research is growing concerning the experiences of clients from marginalized groups. To date, almost no research explores the professional experiences of therapists from marginalized groups. This qualitative study explores how exclusion operates in the profession among colleagues.